Effects of Values Formation on the Behavior Modification of Grade Two Pupils - Villacarlos, Janeth (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of values formation on the behavior modification of Grade Two pupils in selected public elementary schools. Anchored on the premise that early childhood is a critical period for character development, the research aimed to determine the extent to which values formation influences pupils’ behaviors in terms of honesty, respect for others, kindness, cooperation, responsibility, empathy, and compassion. It also described the profile of teacher-respondents according to age, sex, civil status, position title, educational attainment, length of service, and in-service trainings attended; identified problems encountered by teachers regarding pupils’ behavior; and tested whether significant differences existed in respondents’ perceptions when grouped according to profile variables.The study employed a descriptive survey research design using a researcher-made questionnaire-checklist validated by experts in education, research, and statistics. A total of 104 teachers participated as respondents. Data were collected through Google Forms in compliance with the Data Privacy Act and analyzed using the Statistical Package for the Social Sciences. Weighted mean was utilized to measure the extent of effects and problems encountered, while the F-test determined significant differences in perceptions.Findings revealed that values formation had a very high extent of positive effects on pupils’ behavior across all seven dimensions, with behaviors consistently manifested at an “Always” level. Teachers reported that behavioral concerns were encountered only to a “Sometimes” extent, with lack of gratitude identified as the most common issue. Inferential analysis showed no significant differences in perceptions across respondents’ demographic characteristics. The study concluded that values formation plays a vital role in enhancing positive behavior among Grade Two pupils. An action plan was proposed to strengthen school-based values education programs and promote sustained behavioral development.